Phubbing By Gen-Z And Gen-Y: Exploring Smartphone Usage And Its Implications On Interpersonal Communication In The Workplace - Bonifacius Sandro Dwi Atmaja; Silvanus Alvin (Publikasi Indonesia, 2023)
This research examines